Outcomes following mycophenolate mofetil versus cyclophosphamide induction treatment for proliferative juvenile-onset lupus nephritis. (April 2019) - Smith, EMD; Al-Abadi, E; Armon, K; Bailey, K; Ciurtin, C; Davidson, J; Gardner-Medwin, J; Haslam, K; Hawley, D; Leahy, A; Leone, V; McErlane, F; et al.
Background: Juvenile-onset systemic lupus erythematosus (JSLE) is more severe than adult-onset disease, including more lupus nephritis (LN). Despite differences in phenotype/pathogenesis, treatment is based upon adult trials. This study aimed to compare treatment response, damage accrual, time to inactive LN and subsequent flare, in JSLE LN patients treated with mycophenolate mofetil (MMF) versus intravenous cyclophosphamide (IVCYC). Methods: UK JSLE Cohort Study participants, ≤16 years at diagnosis, with ≥4 American College of Rheumatology criteria for SLE, with class III or IV LN, were eligible. Mann–Whitney U tests, Fisher's exact test and Chi-squared tests were utilized for statistical analysis. Results: Of the patients, 34/51 (67%) received MMF, and 17/51 (33%) received IVCYC. No significant differences were identified at 4–8 and 10–14 months post-renal biopsy and last follow-up, in terms of renal British Isles Lupus Assessment Grade scores, urine albumin/creatinine ratio, serum creatinine, ESR, anti-dsDNA antibody, C3 levels and patient/physician global scores. Standardized Damage Index scores did not differ between groups at 13 months or at last follow-up. Inactive LN was attained 262 (141–390) days after MMF treatment, and 151 (117–305) days following IVCYC ( p  = 0.17). Time to renal flare was 451 (157–1266) days for MMF, and 343 (198–635) days for IVCYC ( p  = 0.47). Conclusion: This is the largest study to date investigating induction treatments for proliferative LN in children, demonstrating comparability of MMF and IVCYC.